LEGAL PROTECTION OF REGISTERED COSMETIC BRAND - Miftah Arifin; Wijayono Hadi Sukrisno; Zaenal Arifin; Wiwin Setyorini (UNTAG Law Review, 2022)
The purpose of this study is to analyze the legal protection of registered cosmetic brands, analyze the obstacles and solutions in the legal protection of cosmetic brands. This study uses a qualitative descriptive research method with a normative juridical approach. The results of this study are the legal protection against counterfeiting of well-known trademarks in Indonesia is regulated by Law Number 8 of 1999 concerning Consumer Protection and Law Number 20 of 2016 concerning Trademarks and Geographical Indications, but because brand protection is still a delict complaint and has not been maximized without a complaint from the brand holder and no sanctions are applied for brand infringement, so that supervision is needed by the Department of Industry and Trade throughout Indonesia in thedistribution of goods to traders in order to prevent the circulation of counterfeit goods Obstacles in carrying out legal protection against cosmetic counterfeiting regardinglegal regulation and law enforcement, cosmetic brand products that are still widelycounterfeited and cheap prices, lack of facilities and facilities that support tools that make it easy to detect an item and fifth, namely the weak awareness of buyers to buy a quality item. The problem solving are such as make regional regulations regarding brand counterfeiting in each region, to suppressing brand counterfeiting by providing socialization to business actors and the public about the dangers of brand counterfeiting, especially those containing ingredients that are harmful to health.